UHPLC-ESI-QTOF-MS/MS Metabolite Profiling of the Antioxidant and Antidiabetic Activities of Red Cabbage and Broccoli Seeds and Sprouts - Simon-Okomo Aloo; Fred-Kwame Ofosu; Eric-Banan-Mwine Daliri; Deog-Hwan Oh (Antioxidants, 2021)
The antioxidant and antidiabetic properties and metabolite profiling of ethanol extracts of red cabbage (RC) and broccoli (BR) seeds and sprouts were investigated in this study. The total phenolic, flavonoid, and saponin contents were in the ranges of 385.4–480.4 mg FAE/100 g, 206.9–215.6 mg CE/100 g, and 17.8–27.0 mg soysaponin BE/100 g, respectively. BR seed had the highest total phenolic (480.4 mg FAE/100 g) and flavonoid (216.9 mg CE/100 g) contents, whereas BR sprout had the highest saponin content (27.0 soysaponin BE/100g). RC sprout demonstrated the highest antioxidant capacity, with DPPH and ABTS radical scavenging activity levels of 71.5% and 88.5%, respectively. Furthermore, BR and RC sprouts showed the most potent inhibition against α-glucosidase (91.32% and 93.11%, respectively) and pancreatic lipase (60.19% and 61.66%, respectively). BR seed (60.37%) demonstrated the lowest AGE inhibition. A total of 24 metabolites, predominantly amino acids and phenolic compounds, were characterized using UHPLC-QTOF-MS/MS. Germination not only improved the levels of metabolites but also resulted in the synthesis of new compounds. Therefore, these findings show that germination effectively enhanced the functional properties and metabolite profiles of broccoli and red cabbage seeds, making their sprouts more applicable as functional ingredients.